1992
DOI: 10.1037/0735-7044.106.5.789
|View full text |Cite
|
Sign up to set email alerts
|

Increased training in an aversively motivated task attenuates the memory-impairing effects of posttraining N-methyl-D-aspartate-induced amygdala lesions.

Abstract: This study was designed to examine the effect of variations in the amount of preoperative training on the retention deficit produced by posttraining lesions of the amygdaloid complex (AC). Rats received 1, 10, or 20 training trials in a footshock-motivated escape task 7 days before receiving N-methyl-D-aspartate lesions of the AC. Inhibitory avoidance retention performance, which was measured 4 days postoperatively, indicated that increased training improved retention in AC-lesioned animals as well as in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
3
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 39 publications
13
62
3
1
Order By: Relevance
“…In addition, it is shown here that amygdala neurons are involved in the acquisition of the instrumental response, centered in the limbic thalamus and cingulate cortex. These findings may also account for the recent findings suggesting that the role of the amygdala is time-limited, i.e., necessary for the acquisition but not the maintenance of some types of associative learning (Brady et al, 1954;Thatcher and Kimble, 1966;Aigner et al, 1991;Parent et al, 1992Parent et al, , 1995Roozendaal et al, 1993;Burns et al, 1994). The amygdala is necessary for initiating the training-induced changes in the limbic thalamus, but once initiated, the amygdalar involvement is reduced.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, it is shown here that amygdala neurons are involved in the acquisition of the instrumental response, centered in the limbic thalamus and cingulate cortex. These findings may also account for the recent findings suggesting that the role of the amygdala is time-limited, i.e., necessary for the acquisition but not the maintenance of some types of associative learning (Brady et al, 1954;Thatcher and Kimble, 1966;Aigner et al, 1991;Parent et al, 1992Parent et al, , 1995Roozendaal et al, 1993;Burns et al, 1994). The amygdala is necessary for initiating the training-induced changes in the limbic thalamus, but once initiated, the amygdalar involvement is reduced.…”
Section: Discussionsupporting
confidence: 54%
“…The present finding that afferent limb emotional conditioning processes are essential for the cingulothalamic changes that support instrumental avoidance learning provides the first putative identification of separate neuroanatomical substrates of the two processes, as well as anatomical and physiological links between them. This suggested division of function is also supported by the demonstrations that (1) acquisition and maintained performance of aversively motivated Pavlovian conditioned responses (CRs) require an intact amygdala (Weisz et al, 1992;Lee et al, 1996;; (2) acquisition and performance of at least one variety of aversively motivated Pavlovian CR, the eye blink CR, do not require intact cingulothalamic circuitry ; and (3) the contribution of the amygdala to aversively motivated instrumental learned responses diminishes as experience accumulates in a given task (Parent et al, 1992;Roozendaal et al, 1993;Poremba and Gabriel, 1995).…”
Section: Implications For F Unctional Organization Of the Learning-rementioning
confidence: 82%
“…In contrast to inhibitory avoidance, amygdalar lesions made either shortly (1 day) or long (7 or 28 days) after training effectively abolish conditioned freezing response (Maren et al, 1996a). Surprisingly, extensive overtraining mitigates amygdalar-lesion effects on fear conditioning (Kim and Davis, 1993), as well as inhibitory avoidance (Parent et al, 1992). Although these results indicate that the amygdala is a component of multiple fear systems in the brain, the fact that amygdala lesions (and inactivation) effectively abolish initial fear conditioning suggests that the amygdala may be the default fear learning structure.…”
Section: Brain Areas Other Than the Amygdalamentioning
confidence: 97%
“…Recall that Pavlovian fear conditioning and inhibitory avoidance are considered to be two procedurally different fear tasks. McGaugh and colleagues reported that although amygdalar lesions affect inhibitory avoidance learning, animals can still learn and retain fear when they are overtrained, which indicates that the amygdala is not necessary for fear learning (Parent et al, 1992). Rats that received more training prior to lesions also exhibited far greater retention of inhibitory avoidance memory.…”
Section: Permanent Storage Site(s) Of Fear Memorymentioning
confidence: 97%